Vertical and horizontal location of the mental foramen in relation to the mandibular second premolar by the radiograph method - Felipe Paes Varoli; Julio Cézar de Melo Castilho; Edmundo Médici Filho; Luiz César de Moraes; Luiz Roberto Coutinho Manhães Junior; Mari Eli Leonelli de Moraes; Jeferson Xavier (Faculdade São Leopoldo Mandic, 2008)
Objective: Measure the distance in millimeters, between the apex and the long axis of the mandibular second premolar and the mental foramen. Methods: One hundred and four panoramic radiographs of adults with teeth were selected. Measurement was performed by digitizing the radiographs. The "Image Tool 1.28" program was used to identify the distances. The data of 67 radiographs out of the total, whose visualization of the foramen on the right and left sides was considered good, were submitted to the Student's-t test and Wilcoxon Sign Test Sinais de Postos de Wilcoxon with a=5%. Results: Analyzing the distance from the long axis to the foramen in the 104 radiographs, it was found located at the medial, 73.34% on the right and 69.04% on the left, being the highest percentages. In the distance between the apex and the foramen, the two sides wererelated, t(t=1.07; gl=66; p=0.288), on the right being (median; mean±standard deviation: 4.73; 4.88±3.46) and on the left (5.45;5.23±3.68) and from the long axis to the foramen, relating the sides, parametric (t=1.98; gl=66; p=0.051) and non-parametric (p=0.081), indicating on the right (median; mean±standard deviation: 4.02; 3.81±4.03) and on the left (3.79; 2.78±4.15). The results indicated that the mental foramen was presented medially to the 2nd premolar, being correspondent to the sides, both to a mean of, right, 4.88mm from the apex and 3.81 mm in the mesial direction; and left, 5.23mm from the apex and 2.78mm in the mesial direction. Conclusion: It could be concluded that both the distance from the apex and from the long axis did not differ statistically toward the right and left.